Znaczenie kultury organizacyjnej w zarządzaniu jakością - Szczepańska, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article present chosen aspects and relations between systems and a process oriented organisation with culture as one of management determinants. The main factors that create balanced organisational systems should also consider the culture aspects of creation value perspective in quality management system. Modern quality theory and practice are connected with Corporate Governance concept as well as with new challenge for managing development and organisation growth. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1177, s. 253-264